2021
DOI: 10.3390/ijms222011101
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of Clinical Relevance via Telomere Maintenance Mechanism

Abstract: Understanding the telomere maintenance mechanism (TMM) in immortal cancer cells is vital for TMM-targeted therapies in clinical settings. In this study, we classified four telomere maintenance mechanisms into telomerase, ALT, telomerase + ALT, and non-defined telomere maintenance mechanism (NDTMM) across 31 cancer types using 10,704 transcriptomic datasets from The Cancer Genome Atlas. Our results demonstrated that approximately 50% of the total cohort displayed ALT activity with high telomerase activity in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…This was similar to a study that reported approximately 30–40% and 30% ALT activity in a GC cohort and in tumor cells of another cohort, respectively [ 5 ]. Specifically, in endothelial cells, granulocytes, and macrophages, the number of cells exhibiting ALT and telomerase activities was low and relatively high, respectively.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This was similar to a study that reported approximately 30–40% and 30% ALT activity in a GC cohort and in tumor cells of another cohort, respectively [ 5 ]. Specifically, in endothelial cells, granulocytes, and macrophages, the number of cells exhibiting ALT and telomerase activities was low and relatively high, respectively.…”
Section: Resultssupporting
confidence: 92%
“…By comparing cell type categorization and TMM type in single-cell data subjected to imputation, we determined the TMM types of single cells. TMM types were classified into four categories in order to determine the most prevalent type in each cell, and six pathways were assessed using the gene profile from our previous pan-cancer TMM study [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, emerging studies have implied that TMM in cancer is a complicated process that is associated with hundreds of various genes [ 15 ]. These telomere-related genes (TRGs) have also shown significant relevance to the prognosis of several types of cancer.…”
Section: Introductionmentioning
confidence: 99%